Transformasi Etika Profesi Manajemen Sebagai Penggerak Integritas Dan Keunggulan Organisasi Di Era Modern - Dito Aditia Darma Nst; Rivaldy Amor Naposo Harahap; Kesia Manalu; Dheo Pradika; M. Satya Adifka; Tety Januarti; Risky Syahputra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Management professional ethics play an important role in shaping the integrity and excellence of organizations, especially in the modern era marked by digitalization, globalization, and the complexity of market dynamics. This article aims to analyze the transformation of management professional ethics and its impact on organizational integrity and performance. The research approach used is a systematic literature study, by reviewing various recent studies on ethics, leadership, and organizational governance. The results of the study show that professional ethics is not only a normative moral guideline, but also a strategic framework that directs decision-making, organizational behavior, and management policies. The consistent application of ethics has been proven to improve internal integrity, build a positive work culture, and strengthen stakeholder trust. In addition, ethically-based organizations are able to gain a competitive advantage through reputation, employee loyalty, and harmonious relationships with stakeholders. However, ethical challenges in the modern era are increasingly complex, arising from digitalization, market pressures, and conflicts of interest. This article concludes that the transformation of the ethics of the management profession is the driving force for integrity and the foundation of organizational excellence, as well as the key to the success of the organization in facing modern challenges in a sustainablemanner. Keywords: management professional ethics, organizational integrity, organizational excellence, leadership, modern era.